Działacze chłopscy wobec kolektywizacji wsi zielonogórskiej w latach 1948-1956 = Peasant activists' involvement in the collectivisation in Zielona Góra country in 1948-1956 - Koteluk, Daniel; Matusiak, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Along with the abolition of the independent peasant movement, the communist party made the peasant activists implement its agricultural policy. One of its pillars was the creation of collective farms. The collectivisation was supposed to make independent farmers dependent economically on the Polish Workers' Party (PPR) - since December 1948, the Polish United Workers' Party (PZPR). Thence the United Peasant Movement's (PSL) authorities' drive to collectivise the country.
Keywords: PZPR (Polska Zjednoczona Partia Robotnicza); PPR (Polska Partia Robotnicza); kolektywizacja; Polska - historia - od 1944 r.